Sinergi Manajerial dan Kepemimpinan Transformasional dalam Mendorong Kinerja Guru Sekolah Dasar - Yuda Prihatono; Aan Komariah; Deni Kadarsah (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2025)
Abstract: This study aims to examine the effects of principals’ managerial competence and transformational leadership on the performance of elementary school teachers in Purwakarta District. The research employed a quantitative approach using an explanatory research design. The sample consisted of 290 elementary school teachers selected through proportional random sampling. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling (SEM) and Multi-Group Analysis (MGA) to identify differences in effects between public and private schools. The results indicate that elementary school teachers’ performance is generally in the good category, as reflected in lesson planning, instructional implementation, classroom management, student participation, and learning assessment. Structurally, principals’ managerial competence has a positive and dominant effect on teacher performance, with a path coefficient of 0.512, while transformational leadership also shows a positive effect with a coefficient of 0.245. Together, both leadership dimensions explain 62.2% of the variance in teacher performance. The MGA results reveal differences based on school type, showing that managerial competence is more dominant in public schools, whereas transformational leadership has a stronger influence in private schools. This study concludes that improving teacher performance is most effective when school principals are able to integrate strong managerial competence as the foundation of school governance with transformational leadership as a driver of motivation and school culture. Therefore, leadership development programs for school principals should be designed holistically and contextually, taking into account the characteristics and needs of different school types. Keywords: Managerial capability, School principal, Teacher performance, Transformational leadership. Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh kemampuan manajerial dan kepemimpinan transformasional kepala sekolah terhadap kinerja guru sekolah dasar di Kecamatan Purwakarta. Penelitian menggunakan pendekatan kuantitatif dengan metode explanatory research. Sampel penelitian terdiri atas 290 guru sekolah dasar yang dipilih menggunakan teknik proportional random sampling. Data dikumpulkan melalui kuesioner terstruktur dan dianalisis menggunakan Structural Equation Modeling (SEM) serta Multi-Group Analysis (MGA) untuk mengidentifikasi perbedaan pengaruh berdasarkan jenis sekolah (negeri dan swasta). Hasil penelitian menunjukkan bahwa kinerja guru sekolah dasar berada pada kategori baik, ditinjau dari aspek perencanaan pembelajaran, pelaksanaan pembelajaran, pengelolaan kelas, partisipasi siswa, dan penilaian pembelajaran. Secara struktural, kemampuan manajerial kepala sekolah berpengaruh positif dan paling dominan terhadap kinerja guru dengan koefisien jalur sebesar 0,512, sedangkan kepemimpinan transformasional juga berpengaruh positif dengan koefisien sebesar 0,245. Kedua variabel tersebut secara simultan menjelaskan 62,2% variabilitas kinerja guru. Hasil analisis MGA menunjukkan adanya perbedaan dominansi pengaruh berdasarkan jenis sekolah, di mana kemampuan manajerial lebih dominan pada sekolah negeri, sementara kepemimpinan transformasional lebih berpengaruh pada sekolah swasta. Penelitian ini menyimpulkan bahwa peningkatan kinerja guru akan optimal apabila kepala sekolah mampu mengintegrasikan kemampuan manajerial sebagai fondasi tata kelola sekolah dan kepemimpinan transformasional sebagai penggerak motivasi serta budaya kerja. Oleh karena itu, pengembangan kepemimpinan kepala sekolah perlu dirancang secara holistik dan kontekstual sesuai karakteristik sekolah. Kata kunci: Kepala sekolah, Kemampuan manajerial, Kepemimpinan transformasional, Kinerja guru.